Strategies to Promote Stronger Technology Spillovers From Trade and Investments: Tapping Production Networks, Promoting Services and Linking SMEs - Mendoza, Ronald U (Archīum Ateneo, 2013)
Trade and investment flows into less advanced economies could bring about important technological spillovers that could boost firm-level productivity and bolster their long term economic growth. This brief paper outlines some of the motivations for public sector interventions to support learning by doing and stronger technological spillovers. It then provides a brief discussion of three key areas for policy attention, covering a) the features that make international production networks fertile platforms for these spillovers; b) the opportunities for technology spillovers in the services sector; and c) the challenges associated with policies to link SMEs into these sectors that are fertile ground for technology spillovers and innovation. This paper concludes by presenting a few possible guidelines on innovation and technology policy based on the lessons of industrialization attempts in the last several decades.